Variation in photosynthetic induction between rice accessions and its potential for improving productivity. Issue 4 (3rd March 2020) - Acevedo‐Siaca, Liana G.; Coe, Robert; Wang, Yu; Kromdijk, Johannes; Quick, W. Paul; Long, Stephen P.
Summary: Photosynthetic induction describes the transient increase in leaf CO2 uptake with an increase in light. During induction, efficiency is lower than at steady state. Under field conditions of fluctuating light, this lower efficiency during induction may cost > 20% of potential crop assimilation. Accelerating induction would boost photosynthetic and resource‐use efficiencies. Variation between rice accessions and potential for accelerating induction was analysed by gas exchange. Induction during shade to sun transitions of 14 accessions representing five subpopulations from the 3000 Rice Genome Project Panel (3K RGP) was analysed. Differences of 109% occurred in the CO2 fixed during the first 300 s of induction, 117% in the half‐time to completion of induction, and 65% in intrinsic water‐use efficiency during induction, between the highest and lowest performing accessions. Induction in three accessions with contrasting responses (AUS 278, NCS 771 A and IR64‐21) was compared for a range of [CO2 ] to analyse limitations. This showed in vivo capacity for carboxylation at Rubisco ( V c, max ), and not stomata, as the primary limitation to induction, with significant differences between accessions. Variation in nonsteady‐state efficiency greatly exceeded that at steady state, suggesting a new and more promising opportunity for selection of greater crop photosynthetic efficiency in this key food crop. Abstract : See also the Commentary on this article by McAusland & Murchie, 227 : 989–991 .